VARIOUS LABIAL BOW MODIFICATION IN REMOVABLE ORTHODONTIC APPLIANCE - Dewi, Ajeng Firliana; Rusdiana, Elly; Goenharto, Sianiwati (Journal of Vocational Health Studies, 2019)
Background: In several dental malposition cases, removable orthodontic component modifications are needed in order to obtain maximum end result, and comfortable to use. One of the active components which can be modified is the labial arch. Purpose: To identify various labial bow modifications in the removable orthodontic appliance. Review: Labial bow can be modified according to patient need. The modification can be used to correct dental arches, canine retraction, and correcting teeth extrusion. The variations include labial arch with M-loop, labial arch with canine retraction loop, labial arch with loop on canine, and labial arch with Andresen loop. Another modification is a labial bow with the addition of soldered hook and coil to put an elastic. Conclusion: Labial bow has various modifications in a removable orthodontic appliance according to the function required.